2021
DOI: 10.1542/hpeds.2020-004788
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Versus Prednisone in Children Hospitalized for Acute Asthma Exacerbations

Abstract: BACKGROUND AND OBJECTIVES Extensive literature supports using dexamethasone (DEX) in children presenting to the emergency department (ED) with mild-to-moderate asthma exacerbations; however, only limited studies have assessed this in hospitalized children. In this study, we evaluate the outcomes of DEX versus prednisone/prednisolone (PRED) use in children hospitalized for mild-to-moderate asthma exacerbations. METHODS This mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…13,2125 Studies comparing dexamethasone versus alternative systemic corticosteroids for pediatrics are largely observational, limited to the emergency department setting, and focused on relapse rates or acute asthma severity clinical scores as primary endpoints. 12,14,15,2629…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…13,2125 Studies comparing dexamethasone versus alternative systemic corticosteroids for pediatrics are largely observational, limited to the emergency department setting, and focused on relapse rates or acute asthma severity clinical scores as primary endpoints. 12,14,15,2629…”
Section: Discussionmentioning
confidence: 99%
“…Observational comparative studies have reported two daily doses of dexamethasone are as equivalent to a 5-day course of prednisone or methylprednisolone. 12,16,29 In the emergency department setting this may improve discharge medication compliance. 35 A shorter corticosteroid regimen may diminish pharmacologic-related hospital charges.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations